Performance Pay and Productivity in Health Care: Evidence from Community Health Centers - Brian C. Cadena; Austin C. Smith (Institute of Labor Economics (IZA), 2019)
Nearly half of high earning workers receive performance pay as part of their compensation, but we know strikingly little about the incentive effects of piece rate compensation on high-skilled workers. In this paper, we examine changes in medical providers' output in response to a piece rate compensation scheme. We use data from a Federally Qualified Health Center that changed from a salary-based plan to one that rewarded providers for seeing more patients on a monthly basis. Two key facts guide our empirical approach. First, the timing of the switch from salary to piece rates varied at the individual level depending on the provider's hire date, which allows us to control for other changes over time in patient demand for services. Second, most providers worked under both compensation schemes, which allows us to make within-person comparisons. We further address incomplete compliance by using providers' expected monthly compensation plan status as an instrument for their actual status. We find that providers working under the piece rate scheme see roughly 18 percent more patients monthly. Only a small portion of this difference is due to within-provider changes in output, and we find no evidence that the incentive scheme causes providers to become more productive. Instead, most of this difference derives from compositional changes in the workforce, likely due to increased retention of more productive providers.
Keywords: J22; J33; 330; piece rates; performance pay; medical providers; fee for service